Kualitas Pelayanan Pendidikan Islam dalam Mencapai Kepuasan Pelanggan/Peserta Didik diI MTS Pacet Mojokerto - Novira; Zakariyah Zakariyah; Rudolf Chrysoekamto (LPPM IAI Hasanuddin Pare-Kediri, 2020)
This study aims to describe and measure: (1) Quality of educational services at the MTs Pacet Mojokerto Surban Foundation (2) Customer satisfaction / education students at the MTs Pacet Mojokerto Surban Foundation. While the purpose of the study is to explain and analyze the quality of service, customer / student satisfaction, and supporting factors customer / student satisfaction at the Surban Foundation MTs Pacet Mojokerto. The type of research used is descriptive qualitative using an intensive case study approach, illuminating important variables, processes and interactions that require extensive attention. The results of this study are: (1) The quality of Islamic education services at the MTs Pacet Surban Foundation is achieved. This is shown by the active role of all elements of education through cooperation and continuous improvement, (2) Satisfaction of education customers / students at the Surs Foundation MTs Pacet is marked by the final results that become a reference, increased memorization and availability following additional hours..